Differences in source selection and their effect on the quality of written statements during a critical online reasoning performance assessment - Braunheim, Dominik; Martin De Los Santos Kleinz, Lisa; Trierweiler, Lukas (Frontiers in Computer Science, 2024)
The importance of researching information on the Internet is ever increasing. While ease of use and accessibility are advantages, there is a risk of not being able to adequately assess the relevance and reliability of online sources. With data from the Bridge-project (N=143) we assess the online movements of respondents and track how they researched digitally to answer a task on a generic, accessible topic. We then draw conclusions about their search behavior during this open online performance assessment. The controlled and monitored environment allowed to identify differences in their source selection and how those had an impact on the quality of their written statements respective to the given task.